1975
DOI: 10.1073/pnas.72.5.1792
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the human gene for hypoxanthine-guanine phosphoribosyltransferase via isolated human metaphase chromosomes into mouse L-cells.

Abstract: We have transferred the human gene for hypoxanthine-guanine phosphoribosyltransferase (HPRT, EC 2.4.2.8; IMP: pyrophosphate phosplioribosyltransferase) via isolated metaphase chromosomes from human HeLa S3 cells into murine A9 cells which lack functional murine HPRT activity, using the technique of McBride and Ozer (Proc. Nat. Acad. Sci. USA 70,[1258][1259][1260][1261][1262] 1973

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…The HRASI-selected transformants were analyzed for cotransfer of each of the nine gene markers shown in Fig. 1 (40b), based on the combined results from deletion and transl9cation mapping in hybrid cells (4,11,12,13,39,42), in situ hybridization analysis of mitotic chromosomes (44), and family linkage data with segregating polymorphic markers (15,41). Cells and culture conditions.…”
mentioning
confidence: 99%
“…The HRASI-selected transformants were analyzed for cotransfer of each of the nine gene markers shown in Fig. 1 (40b), based on the combined results from deletion and transl9cation mapping in hybrid cells (4,11,12,13,39,42), in situ hybridization analysis of mitotic chromosomes (44), and family linkage data with segregating polymorphic markers (15,41). Cells and culture conditions.…”
mentioning
confidence: 99%
“…The initial success of chromosome transfer experiments was followed by the transfer of a variety of human and rodent genes into mutant recipient cell lines (24,25). The frequency of transfer, however, was very low in the presence of poly-lysine buffer used by McBride and Ozer (21).…”
Section: Chromosome Transfer In Mammalian Cellsmentioning
confidence: 99%
“…In several other laboratories, it was confirmed that the genetic information from isolated mammalian chromosomes was transferred into recipient cells by the chromosome immigration method (McBride and Ozer, 1973;Shani et a[., 1974;Willecke and Ruddle, 1975;Burch and McBride, 1975;Shani et al, 1976). However, with the chromosome immigration method, it is very difficult to pick up a single cell into which chromosomes have immigrated.…”
mentioning
confidence: 94%